2004
DOI: 10.1097/01.tp.0000144332.44435.ab
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ??-Melanocyte???Stimulating Hormone on Renal Tubular Cell Apoptosis and Tubulointerstitial Fibrosis in Cyclosporine A Nephrotoxicity

Abstract: These findings suggest that chronic CsA nephrotoxicity is related to Bax and Bcl2-related apoptosis pathways, and that alpha-MSH can attenuate the CsA-induced tubulointerstitial fibrosis as well as tubular cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…Tubular cell apoptosis is also observed in animal [107][108][109] and cell culture models [110,111]. Cyclosporine-induced apoptosis is primarily triggered through the mitochondrial pathway.…”
Section: Typical Examples Of Apoptosis Induced By Nephrotoxic Agentsmentioning
confidence: 94%
“…Tubular cell apoptosis is also observed in animal [107][108][109] and cell culture models [110,111]. Cyclosporine-induced apoptosis is primarily triggered through the mitochondrial pathway.…”
Section: Typical Examples Of Apoptosis Induced By Nephrotoxic Agentsmentioning
confidence: 94%
“…A recent report showed that collagen metabolism is a novel target of α-MSH [18]. It attenuated procollagen synthesis in experimental heart transplantation and reduced tubulointerstitial fibrosis in cyclosporine A (CsA)-induced nephrotoxicity [19,20]. Besides, α-MSH is known to increase collagenolytic activity by activating MMP-1 and MMP-2 [21,22].…”
Section: Introductionmentioning
confidence: 97%
“…18 It attenuated procollagen synthesis in experimental heart transplantation and reduced tubulointerstitial fibrosis in cyclosporine A-induced nephrotoxicity. 19,20 Besides, a-MSH is known to increase collagenolytic activity by activating MMP-1 and MMP-2.…”
Section: Introductionmentioning
confidence: 99%